2013
DOI: 10.5194/ms-4-199-2013
|View full text |Cite
|
Sign up to set email alerts
|

ROBOTRAN: a powerful symbolic gnerator of multibody models

Abstract: Abstract. The computational efficiency of symbolic generation was at the root of the emergence of symbolic multibody programs in the eighties. At present, it remains an attractive feature of it since the exponential increase in modern computer performances naturally provides the opportunity to investigate larger systems and more sophisticated models for which real-time computation is a real asset.Nowadays, in the context of mechatronic multibody systems, another interesting feature of the symbolic approach app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…In detail we considered stepping on elevated surfaces (50 cm), large stepping (65 cm), squatting and swaying with 50 kg weight, landing on a single foot from 0.35 m, reactive stepping (forward and lateral) and falling (forward and lateral). The simulations were performed with an open source compliant joint simulator based on Robotran multibody modeling tool [16]. More details on these tasks and specification results can be found in a related work [17].…”
Section: Design For Robustnessmentioning
confidence: 99%
“…In detail we considered stepping on elevated surfaces (50 cm), large stepping (65 cm), squatting and swaying with 50 kg weight, landing on a single foot from 0.35 m, reactive stepping (forward and lateral) and falling (forward and lateral). The simulations were performed with an open source compliant joint simulator based on Robotran multibody modeling tool [16]. More details on these tasks and specification results can be found in a related work [17].…”
Section: Design For Robustnessmentioning
confidence: 99%
“…showed that trajectory optimization of gait for a quadrupedal robot modeled with RobCoGen was five times faster with AD than with FD [27]. Other packages for robotic applications with modules supporting AD include Drake [28], Robotran [29], MBSlib [30], and Pinocchio [31]. Drake is a collection of tools that relies on Eigen [32] for linear algebra.…”
Section: Introductionmentioning
confidence: 99%
“…In order to model contact interactions between multibody systems and granular media, the NSCD formalism is extended to the equations of motion of articulated chains. In the proposed approach, the configuration of the latter is described using relative coordinates, according to the methodology detailed in [26,27]. Therefore, for a tree-like system (i.e., without any kinematic loop), the dynamics equation for a smooth motion without contact does not involve constraint equations and can be formulated as follows:…”
Section: Nscd Extension To Mbsmentioning
confidence: 99%